(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This study examines methods for increasing the efficiency of managerial activity in production enterprises under conditions of uncertainty. Modern production systems operate in dynamic economic environments characterized by incomplete information, market fluctuations, and political and technological risks. Managerial efficiency depends on the ability to anticipate, evaluate, and mitigate these uncertainties through a combination of classical management principles, innovative technologies, and human-centric approaches. The research employs a mixed-methods design, combining surveys, interviews, and secondary data analysis to evaluate current managerial practices, identify efficiency-enhancing strategies, and assess the impact of uncertainty on decision-making. Key findings highlight the importance of adaptive management, predictive and preventive measures, integration of digital technologies, strategic flexibility, and participative decision-making. A synergetic approach that combines quantitative and qualitative analyses is recommended to optimize managerial performance, ensure sustainable growth, and maintain a competitive advantage in production enterprises.